ASSESSING PRESIDENTIAL REGULATION NUMBER 125 OF 2016 CONCERNING HANDLING OF REFUGEES FROM ABROAD IN ACEH PROVINCE, INDONESIA - Mukhlis, Mukhlis; Malahayati, Malahayati; Ardila, Saddatun; Muammar, Muammar (Universitas Syiah Kuala, 2023)
The arrival of refugees in Aceh province, specifically the Rohingya from other countries, initially received assistance from the Acehnese people while they were in the middle of the sea. However, in the following years, various challenges have arisen. As a response to this situation, Presidential Regulation No. 125 of 2016 was established to address the handling of refugees from abroad. This regulation highlights the role of the Central Government. However, there is currently no operational regulation from the local government regarding budgets, adaptation to customary values and local wisdom, and coordination with relevant institutions such as UNHCR, IOM, volunteers, police, and other organizations. It is crucial to establish Standard Operating Procedures that can serve as a reference for all parties involved in the process of locating, searching, and assisting refugees from abroad. Additionally, there is a need for the establishment of immigration detention centers in Aceh, as the current temporary shelters are only available in the cities of Lhokseumawe and North Aceh.